2008
DOI: 10.1080/03098770802538129
|View full text |Cite
|
Sign up to set email alerts
|

Learning from experience: the expectations and experiences of first‐year undergraduate psychology students

Abstract: Single-honours psychology students at an English university were asked about their expectations and experiences at the start and the end of their first year. Students without a pre-university (A-level) qualification in psychology (n537: 22%) felt less well-prepared for studying psychology than students with an A-level qualification (n5132: 78%) at the beginning of the year. Both groups felt equally confident about their understanding of psychology at the end of it. Specific difficulties with research methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The majority of this work focuses on non-traditional students -including college leavers -and highlights the barriers they must overcome if they are to become independent learners (Furlong and Cartmel 2009;Thomas and Quinn 2007). These studies also stress the importance of perceptions, indicating how a mismatch between expectations and academic experience can lead to disengagement with the academic process, and an increased risk of underachievement (Rowley, Hartley, and Larkin 2008). This research has opened the way for a critical investigation of the idea that skills -and students -can be transferred directly from one learning environment to another, for example when direct entry students move from college to university.…”
mentioning
confidence: 97%
“…The majority of this work focuses on non-traditional students -including college leavers -and highlights the barriers they must overcome if they are to become independent learners (Furlong and Cartmel 2009;Thomas and Quinn 2007). These studies also stress the importance of perceptions, indicating how a mismatch between expectations and academic experience can lead to disengagement with the academic process, and an increased risk of underachievement (Rowley, Hartley, and Larkin 2008). This research has opened the way for a critical investigation of the idea that skills -and students -can be transferred directly from one learning environment to another, for example when direct entry students move from college to university.…”
mentioning
confidence: 97%
“…The relationship between spirituality, coping, and hopefulness is one that requires further investigation, particularly among first-year university students. University existence signifies a substantial transition and adjustment phase in a person's life with mental health issues being identified as a matter of concern among undergraduate university students from their first year onward (Cleary, Horsfall, Baines, & Happell, 2010;Das & Mishra, 2010;Rowley, Hartley, & Larkin, 2010). It has been found that the majority of university students who withdraw from university do so in the first year.…”
Section: Introductionmentioning
confidence: 96%
“…Data analysis was guided by relevant themes obtained from the literature on transition; for example, background (Leese, 2010), expectations and experiences (Rowley, Hartley & Larkin, 2008), and processes of making adjustment (Gray, Easton, & Ellison, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Educational expectations can be understood as part of one's habitus, and a mismatch between students' expectation and actual experience can lead to students' withdrawal (Rowley, Hartley, & Larkin, 2008). HE students' age, ethnicity, socio-economic background and family HE history are key attributes to students' preparedness for HE (Leese, 2010;Reay, Crozier, & Clayton, 2010).…”
Section: Introductionmentioning
confidence: 99%